Effect Of Various Renal Biopsy Techniques On Clinico-Physiological Observations In Dogs (Applied Biological Research, 2013)
The present study was aimed at to observe the changes in various  clinico-physiological parameters in dogs subjected to different renal  biopsy techniques. Eighteen mongrel dogs, divided randomly into 3 groups, were subjected to ultrasound-guided biopsy using 14-G Tru cut biopsy needle (group I), ultrasound-guided fine-needle aspiration  biopsy using 18-G spinal needle mounted on 10 ml syringe (group II) and laparoscope-guided biopsy using laparoscopic biopsy forceps(group III). Post biopsy analysis of various parameters like rectal  temperature, heart rate, respiration rate and skin fold tenting test  revealed non-significant difference (P>0.05) at any post-procedural  interval. This indicated that all these renal biopsy techniques in dogs  were safe.
Keywords: Biopsy; clinico-physiological changes; dog; renal